PTU-004 Percutaneous endoscopic gastrostomy care?– prospective evaluation of a simple teaching intervention in improving nursing knowledge and confidence. (17th June 2017) - Conley, TE; Povah, M; Collins, B; Theis, V; Fox, M
Abstract : Introduction: Percutaneous Endoscopic Gastrostomies (PEG) for enteral tube feeding are commonplace - point prevalence 92 per million, 2010 1 . PEG care needs to be delivered by skilled practitioners owing to the potential for complication. Anecdotally, we were concerned by a lack of nursing confidence pertaining to PEG care and subsequently saw opportunity for quality improvement. Aim: To determine baseline levels of nursing knowledge and confidence pertaining to PEG care in our trust; and to develop, deliver, and evaluate the efficacy of a simple teaching programme in improving this baseline. Method: Single centre prospective audit of 83 nurses spanning the medical care group (elderly medicine, gastroenterology, and acute medicine) at Whiston Hospital (September-December 2016). Data was collected using a basic safety screening questionnaire, which sought to establish whether common issues encountered could be dealt with appropriately and safely. This was re-audited following delivery of a teaching intervention. Results: In the acute, post-insertion setting, baseline knowledge was sub-optimal. We identified 39% of staff potentially using PEG tubes too early, reduced to 6% post intervention. Knowledge regarding management of complications varied according to experience. Confidence in intervening in the acute setting was lacking. Just 33% of nurses would be confident in inserting a foley catheter to maintain tract patency in the event of dislodgement, improving to 72% post intervention. Teaching promoted knowledge of potential contraindications to re-insertion, such as an immature tract (improving from 20% to 88% post intervention). When faced with a blocked tube only 55% of nurses expressed confidence in intervening; post education, awareness of using warm water in this scenario rose from 34% to 70%. Baseline knowledge regarding PEG maintenance was acceptable; all nurses were aware of the need to regularly rotate the PEG and that a safe minimum angle of 30 degrees should be maintained during feeding. However, just 18% had heard of the Buried Bumper Syndrome. Conclusion: Baseline knowledge pertaining to the care of the PEG fed patient, and confidence in managing common complications was lacking. A simple, tailored educational session successfully identifies gaps in knowledge, improves confidence, and could deter potentially dangerous behaviour. We hope that increasing the confidence of the workforce will translate into fewer complications, a reduction in the need for re-intervention, and an increased PEG lifespan. Ideally, we would like to extend our program into nursing homes to prevent unnecessary hospital admissions in this already frail patient population. Reference: . BANS: Annual BANS Report, 2011; Artificial Nutrition Support in the UK 2000–2010. Disclosure of Interest: None Declared